ANALYSIS OF NATURAL VARIATION IN OsHKT1;1 GENE SEQUENCE AND GENE EXPRESSION IN RELATION TO SALINITY IN RICE (Oryza sativa L.) - P. T. Do; D. H. Nguyen; H. T. Tang (Journal of Animal and Plant Sciences, 2020)
Rice is a main food crop, but sensitive to salinity. The high affinity K+ transporters (HKTs) have been proven to be important to salt tolerance in plants. In the current study, the natural variations in gene sequence of OsHKT1;1 were investigated for uncovering the potential allelic variants in salt tolerance in rice. Sequence analysis of OsHKT1;1 gene was conducted in the coding and promoter regions of all investigated rice cultivars. There were nine SNPs in the coding sequences and ten SNPs in the promoter sequences. Amongst nine SNPs found in the coding sequences, four were nonsynonymous (C89T, C280T, T536C, A773G) leading to four substituted amino acids P30L, L94F, F179S, and N258S. In silico analysis revealed no potential effects of the substituted amino acids to protein structure, but caused changes in post-translational modifications. In the promoter sequences, eight out of ten SNPs caused to five additions and six deletions of the cis-regulatory elements, in which some of them were shown to be involved in stress responses. OsHKT1;1 geneexpression was analyzed in the roots and leaves in response to different salt concentrations. While the expression of OsHKT1;1 was induced in the leaves at the beginning of salt treatment (day 1 and day 2), it was decreased or unchanged in the roots.
Keywords: OsHKT1; 1; salinity; rice; polymorphism